I_λ-Double statistical convergence of order α in topological groups - Savaş, E. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We introduce а new notion, namely, I_λ-double statistical convergence of order α in topological groups. Consequently, we investigate some inclusion relations between I -double statistical and I_λ -double statistical convergence of order α in topological groups. We also study many other related concepts.